Endocrine sequelae of hematopoietic stem cell transplantation: Effects on mineral homeostasis and bone metabolism - Miglietta, Francesca; Iamartino, Luca; Palmini, Gaia; Giusti, Francesca; Marini, Francesca; Iantomasi, Teresa; Brandi, Maria Luisa (Frontiers in Endocrinology, 2023)
Hematopoietic stem cell transplantation (HSCT) is an established therapeutic strategy for the treatment of malignant (leukemia and lymphoma) and non-malignant (thalassemia, anemia, and immunodeficiency) hematopoietic diseases. Thanks to the improvement in patient care and the development of more tolerable conditioning treatments, which has extended the applicability of therapy to the elderly, a growing number of patients have successfully benefited from HSCT therapy and, more importantly, HSCT transplant-related mortality has consistently reduced in recent years. However, concomitantly to long term patient survival, a growing incidence of late HSCT-related sequelae has been reported, being variably associated with negative effects on quality of life of patients and having a non-negligible impact on healthcare systems. The most predominantly observed HSCT-caused complications are chronic alterations of the endocrine system and metabolism, which endanger post-operative quality of life and increase morbidity and mortality of transplanted patients. Here, we specifically review the current knowledge on HSCT-derived side-effects on the perturbation of mineral metabolism; in particular, the homeostasis of calcium, focusing on current reports regarding osteoporosis and recurrent renal dysfunctions that have been observed in a percentage of HSC-transplanted patients. Possible secondary implications of conditioning treatments for HSCT on the physiology of the parathyroid glands and calcium homeostasis, alone or in association with HSCT-caused renal and bone defects, are critically discussed as well.